Equilibrium problems and generalized Nash games - Nasri M. (2011)
Mostafa Nasri acknowledges his scholarship for his doctorate studies, granted jointly by CNPq and TWAS. The research of Wilfredo Sosa was partially supported from CONCYTEC (projects STIC-AMSUD) and by Research Institute of the Science Faculty of UNI.